Ritos e representações do Paleolítico: Uma leitura semiótica - Marquetti, Flávia [UNESP]; Funari, Pedro Paulo A. (Universidade Estadual de Ponta Grossa (UEPG), 2011)
The present paper analyzes evidences found on caves of the Paleolithic Era and their possible relation to initiation rites. The analysis is oriented by a semiotic reading, which seeks to perceive a minimal narrative structure within the pictorial representations. These representations unveil a whole universe related to hunting and to horn and phallic references, which establishes a complementary relation with the feminine/cavern and represents an opposition between life and death. For the purposes of this article, elements of the represented scenes were analyzed, such as geographical localization, the colors that were used, and the intention of the representations.
Rites and representations of the Paleolithic: A semiotic reading
Keywords: Color; Narrative; Representation; Rites